Applicability of Transthoracic Contrast Echocardiography for the Diagnosis and Treatment of Idiopathic Pulmonary Arteriovenous Malformations - Deng, Yujiao; Huang, Xin; Wang, Guangyi; Cao, Jian; Wang, Shengshu; Li, Yue; Wang, Yiru; Ye, Jing; Zhang, Peifang; Chen, Xiaotian; Luo, Yukun; He, Kunlun (Frontiers in Cardiovascular Medicine, 2021)
Objective: To explore the preferred test to screen for pulmonary arteriovenous malformations (PAVMs) and to predict the probability of interventional embolotherapy. Methods: We performed a retrospective observational study evaluating patients with idiopathic PAVMs from 2009 to 2019. After clinical evaluation, a total of 105 patients were studied, including 71 patients with positive digital subtraction pulmonary angiography (DSPA) findings and 34 with negative DSPA findings. The following patient data were assessed: blood test, chest radiograph, transthoracic contrast echocardiography (TTCE), and DSPA findings. Results: The majority of patients with idiopathic PAVMs were female (66.2% with positive DSPA findings). We found a good κ-coefficient of 0.77 with strong consistency for interobserver agreement concerning the pulmonary right-to-left shunt (RLS) grade on TTCE, which was superior to conventional chest radiographs. The positive predictive value (PPV) of the radiographic features for PAVMs on DSPA was 0.83 (95% CI 0.64–1.0) and 0.44 for the feasibility of embolotherapy (95% CI 0.19–0.70). The PPV of the shunt grade of PAVMs on DSPA was 0.14 (95% CI 0.01–0.29) for grade 1, 0.74 (95% CI 0.60–0.88) for grade 2, and 0.97 (95% CI 0.92–1.0) for grade 3. The PPVs of pulmonary shunt grades 2 and 3 on TTCE for the feasibility of embolotherapy for PAVMs were 0.21 (95% CI, 0.05–0.36) and 0.87 (95% CI, 0.79–0.99), respectively. Conclusion: TTCE is the preferred screening test for PAVMs. The pulmonary RLS grade on TTCE not only identifies the likelihood of PAVMs but also predicts the probability for embolotherapy.